2010
DOI: 10.1111/j.1600-0447.2010.01627.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of ten-year mortality in severe anorexia nervosa patients

Abstract: Anorexia nervosa in-patients are at high risk of death. This risk can be predicted by both chronicity and seriousness of illness at hospitalization. These elements should be considered as warnings to adapt care provision and could be targeted by treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
3
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 33 publications
9
72
3
2
Order By: Relevance
“…Thus, when comparisons are based on SMRs rather than on disparate mortality rates, elevated mortality in AN may not be out of scale with other psychiatric disorders. Consistent with Arcelus et al [2], and others [70], our analyses revealed higher risk of premature mortality in studies of older participants (based on mean age at entry) and those with relatively few males. However, by extracting additional covariate data, we were able to examine potential confounding.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, when comparisons are based on SMRs rather than on disparate mortality rates, elevated mortality in AN may not be out of scale with other psychiatric disorders. Consistent with Arcelus et al [2], and others [70], our analyses revealed higher risk of premature mortality in studies of older participants (based on mean age at entry) and those with relatively few males. However, by extracting additional covariate data, we were able to examine potential confounding.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies (Fichter et al, 2006;Papadopoulos et al, 2009) mortality in patients with broad AN was elevated at the beginning of the follow-up but decreased over time. Older age at the beginning of treatment in the specialised eating disorder unit elevated the mortality risk in broad AN, which is consistent with findings from earlier studies (Deter et al, 2005;Millar et al, 2005;Huas et al, 2011). About half (45%) of patients with narrow AN and a little over a third (35%) of patients with broad AN had also received inpatient care.…”
Section: Discussionsupporting
confidence: 87%
“…An important finding of our study was that patients with broad BN have approximately a three-fold risk of premature death which is higher than found in most previous studies (Crow et al, 2009;Arcelus et al, 2011;Huas et al, 2011). Huas et al (2012) found that hospital-treated severe bulimia nervosa patients are at high risk of death (mainly suicide).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Contrasting with these reports, Bulik et al (1999) found no difference in the suicide mortality rates among the various types of EDs. Huas et al (2011) identified 6 factors predicting a high mortality risk in severely affected adult AN inpatients: older age, longer duration of ED, history of suicide attempt, misuse of diuretics, intensity of ED symptoms and desired low BMI at admission). Patients with EDs without suicide attempts have a lower suicidal risk.…”
Section: Relationship Between Eds Sib and Suicidal Behaviourmentioning
confidence: 99%